Factors Associated With Late Antiretroviral Therapy Initiation Among People Living With HIV in Southern Iran: A Historical Cohort Study - Afrashteh, Sima; Fararouei, Mohammad; Ghaem, Haleh; Gheibi, Zahra (Frontiers in Public Health, 2022)
Objectives Late initiation of antiretroviral therapy (ART) is associated with poor outcome among people living with HIV (PLHIV) and higher risk of transmission of infection. This study was conducted to identify the determinants of late ART initiation among PLHIV in Southern Iran. Methods A historical cohort study was conducted on 1,326 PLHIV of ≥15 years of age who were registered with the behavioral diseases counseling center (BDCC) in southern Iran from August 1997 to March 2021. Late ART initiation was defined as a CD4 cell count <200 cells/mm3 or having a clinical AIDS diagnosis at the time of ART initiation. The required demographic and clinical data were collected from the patients' medical records. Multiple regression analysis was conducted to define late ART initiation associated factors. Results Late ART initiation was found among 81.9% of patients. Based on the results of the multivariate analysis, older age (odds ratio [OR] = 1.02, 95% CI = 1.00–1.04), being single (ORsingle/married = 1.80, 95% CI = 1.17–2.78), history of drug use (ORyes/no = 1.64, 95% CI = 1.02–2.62), year of ART initiation (OR2011−2013/2018−2021 = 3.65, 95% CI = 2.28–5.86), and possible route of transmission (ORdruginjection/sexual = 7.34, 95% CI = 1.16–46.21) were directly associated with the risk of late ART initiation. Conclusions The results show that the prevalence of late ART initiation was alarmingly high. For better infection control and better prognosis of infection, people at high risk need to be provided with timely services (e.g., diagnosis, treatment, training, and social support).